2023
DOI: 10.3389/fgene.2023.1204463
|View full text |Cite
|
Sign up to set email alerts
|

SETD2-H3K36ME3: an important bridge between the environment and tumors

Abstract: Epigenetic regulation plays an important role in the occurrence, development and treatment of tumors. The histone methyltransferase SET-domain-containing 2 (SETD2) plays a key role in mammalian epigenetic regulation by catalyzing histone methylation and interacting with RNA polymerase II to mediate transcription elongation and mismatch repair. As an important bridge between the environment and tumors, SETD2-H3K36me3 plays an important role in the occurrence and development of tumors. Many tumors, including ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Further analysis revealed that patients responding to ICB therapy (partial response and complete response: PR/CR) exhibited higher SETD2_Y1666C-mutation signature compared with non-response groups (progressive disease and stable disease: PD/SD) (Figure 7F), and the mutation signature also showed a positive correlation with progression-free survival (Figure 7G). Interestingly, recent studies also found that patients with different cancer types that harboring SETD2 deleterious mutations showed improved response to ICB therapy (He et al, 2023; Lu et al, 2021). Collectively, these findings firstly demonstrated the mechanisms of SETD2_Y1666C mutation in modulating immune surveillance and further supported the notion that the mutation is relevant to a better response to ICB treatment in clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis revealed that patients responding to ICB therapy (partial response and complete response: PR/CR) exhibited higher SETD2_Y1666C-mutation signature compared with non-response groups (progressive disease and stable disease: PD/SD) (Figure 7F), and the mutation signature also showed a positive correlation with progression-free survival (Figure 7G). Interestingly, recent studies also found that patients with different cancer types that harboring SETD2 deleterious mutations showed improved response to ICB therapy (He et al, 2023; Lu et al, 2021). Collectively, these findings firstly demonstrated the mechanisms of SETD2_Y1666C mutation in modulating immune surveillance and further supported the notion that the mutation is relevant to a better response to ICB treatment in clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Although K36 methylation is generally considered as an active mark, it is relevant for silencing by DNA methylation (13,14) and for silencing at facultative heterochromatin by H3K27me3 (15,16). In addition, K36me3 has been linked to genome stability (for review, see (70)) and HMTs establishing H3K36 methylation as well as K36me readers have been linked to cancer (7173).…”
Section: Discussionmentioning
confidence: 99%
“…Although K36 methylation is generally considered as an active mark, it is relevant for silencing by DNA methylation ( 13 , 14 ) and for silencing at facultative heterochromatin by H3K27me3 ( 15 , 16 ). In addition, K36me3 has been linked to genome stability (for review, see ( 76 )) and HMTs establishing H3K36 methylation as well as K36me readers have been linked to cancer ( 77–79 ).…”
Section: Discussionmentioning
confidence: 99%